From definition to the operacionalization, with emphasis on the research on violence - Knežić Branislava T. (Temida)
This paper intends to draw attention to the process which starts with definition and ends with operacionalization, and serves the building of notion apparatus as something which precedes the research. Apart from general discussion, the paper includes the overview of definition and operacionalization problems related to the notion of violence. The author concludes that empirical data which are deprived of theoretical and methodological foundation are able neither to discover nor to explain deeper connections and relationships between phenomena. As a result, empirical data without notion framework and scientific aim, in some of research carried out in Serbia during last decade, have limited value.